Femoral osteochondritis of the knee: Prognostic value of the mechanical axis. (February 2017) - Gonzalez-Herranz, P.; Rodriguez, M.L.; de la Fuente, C.
Purpose: Femoral osteochondritis dissecans (OCD) is a disorder of unknown aetiology and variable prognosis that causes knee pain. In this paper, the authors study the impact of lower limb malalignment on the development and prognosis of OCD. Methods: After anteroposterior (AP) and lateral radiograph and MRI of the knee, 53 cases of OCD were diagnosed. All patients were studied by standing full-length AP radiograph of the lower extremities in order to analyse the relationship between the femorotibial and mechanical axis and the location and stability of the osteochondritis. Results: The OCD lesion was located in the medial condyle (zone 2) in 75.5% of cases (40 cases). The lateral condyle was affected in 24.5% of cases (zone 4 in nine cases and zone 5 in four cases). The femorotibial angle (anatomical axis) was normally aligned in 68% of cases. A valgus deformity was observed in 9.5% of cases and a varus deformity in 22.5%. The mechanical axis of the limb appeared normal in only 32% of cases, with medial deviation in 53%, and lateral deviation in 15% of cases. When the OCD lesion was located in the medial condyle (40 cases), the mechanical axis also crossed the knee through the medial zone in 28 cases. When the OCD lesion was located in the lateral condyle (13 cases), the mechanical axis crossed the knee through zones 1 or 2 in four cases. In stable OCD, the mechanical axis and location of the lesion coincided in 19 of 36 cases (52%), compared with 16 of 17 cases (94%) in unstable OCD. Conclusions: There is a high correlation between OCD location and lower limb mechanical axis deviation. The convergence of the mechanical axis with the location of the OCD lesion may be considered an associated factor in fragment instability. This convergence is more common in unstable OCD.